Phytoremediation of African catfish waste using aquatic plant species in peat water - Tutwuri Handayani; Ardianor Ardianor (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Aquatic plants are adaptive living on the gradient of acidity of peat waters in Palangka Raya city, with their potential role in remediating city wastewater. This research is aimed to study the ability of several aquatic plant species to remediate organic wastewater on a laboratory scale. The treatment was done from July to September 2020 in the field laboratory, greenhouse in Palangka Raya, Central Kalimantan. We compared the phytoremediation abilities of aquatic plant species, i.e. water hyacinth (Eichornia crassipes), pickerelweed (Monochoria vaginalis (Burm. F) Presi), water spinach (Ipomoea aquatica), water primrose (Ludwigia ascedences), water lettuce (Pistia stratiotes), giant Salvinia (Salvinia molesta), and hornwort (Ceratophyllum demersum) on the wastewater of African catfish (Clarias gariepinus) by measuring coverage as an indicator of their growth and absorption ability. Physicochemical parameters measured were water level, sunlight intensity, water temperature, electrical conductivity, potential oxidation-reduction, pH, dissolved oxygen, phosphate, nitrate, and ammonia. Results showed that of seven species tested for their phytoremediation abilities on wastewater, giant Salvinia was among the highest reducing total organic matter by about 95%. The highest coverage was water lettuce by 92%, followed by giant Salvinia (79%) and water hyacinth (78%). However, phosphate and ammonia had a negative value of the relative absorption for all aquatic plant species, suggesting a surplus in concentration during incubation. In this case, absorption for phosphate and ammonia is detected from a median of the lowest concentration on each species (n = 4). Water hyacinth and giant Salvinia were the highest absorbing for respectively phosphate and ammonia. Nitrate was absorbed by 100% of all species, except hornwort of 88%. The best absorption of nitrate was by water lettuce. So, it can be concluded that giant Salvinia is the best at absorbing organic waste, followed by water hyacinth; and the best growing by coverage is water lettuce.Keywords:PhytoremediationAquatic plantAfrican catfishWastewaterPeat water